Analisis Implikasi Struktur Aset Perusahaan, Profitabilitas dan Dividend Policy Terhadap Debt Policy - Rona Tumiur Mauli Carolin Simorangkir (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2019)
This research aims to know the influence of Aset Structure, Profitability (ROA), Dividend Policy (DPR) on the debt policy of the firm. This research takes the population from manufacturing companies listed in Indonesia Stock Exchange in 2011-2015. While selected as the sample was 23 manufacturing company. Samples were selected through random sampling method. Analysis techniques in this study using the analysis of multiple linear regression. The research’s result show that either simultaneously, the variable of Aset Structure, Profitability (ROA), Dividend Policy (DPR) influence the debt policy of the firm. It has been proven from the result of (f) simoultant test show significant point of three independent variables that support the hipothesys